Institutional Strengthening of Farmers' Groups in a Joint Empowerment Approach in Lelamase Village, Rasanae Timur District, Bima City - Ardyansah, Ady; Mulyawan, Wawan; Hendra, Hendra; Adilansyah, Adilansyah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze the empowerment processes and institutional strengthening of farmer groups (Gapoktan) in Lelamase Village, Rasanae Timur District, Bima City, through education, training, and farm management development programs. Using a qualitative case study approach, the research involved purposively and snowball-selected informants, including Gapoktan leaders, farmer group members, agricultural extension officers, and local government officials. Data were collected through in-depth interviews, direct observation, and document analysis, and were examined using the interactive Miles and Huberman model, with validity ensured through triangulation and member checking. The findings reveal that institutional strengthening through education and training is highly effective, particularly in improving managerial capacities, practical skills, and technical understanding of both group leaders and facilitators. Farm management development also operates optimally, reflected in improved economic scale, commercial orientation, cooperation with rural cooperatives (KUD), partnerships with relevant stakeholders, and enhanced analysis of local resource and market potential, as well as the diversification of supplementary economic activities. Overall, the synergy among extension services, government support, and farmer group initiatives has successfully enhanced institutional capacity, autonomy, professionalism, and the overall welfare of farmers. These results underscore that structured and continuous empowerment strategies significantly contribute to strengthening agricultural institutions at the local level.